Intellectual property and foreign direct investment: an empirical analysis / Nur Hayati Abd Rahman ... [et al.] - Abd Rahman, Nur Hayati; Abd Samad, Khairunnisa; Daud, Shahreena; Abu Yazid, Zarinah (Universiti Teknologi MARA, Perlis, 2019)
With the help from both domestic and international markets, ASEAN countries are able to catch-up with the latest economic development if they can sustain high economic growth for a long-period of time. To do so, the resources available in the countries such as capital and labors should fully be utilized up to the optimum level. The capital itself, can be in many forms such as investment. Since most of the ASEAN countries are categorized as developing countries, the reliance on foreign direct investment (FDI) as a source of growth is highly needed as it helps the economy to step on a higher stage of economic development via the roles of foreign experts and technological transfer. In ensuring higher level of investment, there is a need to ensure high level of intellectual property protection since it assists in promoting invention, innovation and new business development. In opposite, lacking in protection might discourage foreign investors to invest in the countries, thus limiting the ability of the countries to grow further. Therefore, the aim of this paper is to examine whether strong intellectual property protection will really help in attracting more foreign investors to invest in ASEAN-5 countries. Using annual data from 2007 to 2016, panel data estimation using random effect is employed. It was found that the ASEAN-5 countries should strengthen their intellectual property protection in order to stimulate higher foreign investments. Nevertheless, in between copyright and patents, copyrights protection gives significant effect to the FDI inflows relative to the latter one. It indicates that the countries are slowly moving out from the production-based economy and catching-up towards a digital economy.